Macro-Financial Link and Monetary Policy Management: Insight from the Case of Nepal - Matangi Maskay, Nephil; Pandit, Rajendra (NRB Economic Review, 2011)
Increasing financial sector development and globalization have significantly changed the nature of macro-financial link. The paper aims to obtain insight on how these changes have impacted on the effectiveness of monetary policy management, by undergoing a case study of Nepal. The empirical results over the thirty five year period spanning FY 1975 to FY 2009, find that the elasticity of the real interest rate is not economically and statistically significant in relation to the output gap. This result is further explored by examining sequentially the contributions of direct financing, domestic financial sector development and external integration. The results suggest that while their respective contribution to the elasticity of the real interest rate is now statistically significant, however it remains economically insignificant. Further the direction of effect is opposite to that of the theoretically predicted sign; this contrary result implies that the residual is driving the regression results. The results further suggest that the economic regime shift in early-1990s, had contributed to weaken the elasticity of the real interest rate. The general insight from the Nepalese case study is that countries have to re-examine on a regular basis the nature of macro-financial link to ensure optimal monetary policy management.